Implementation of Digital Transformation at Al-Mahdi Outlets during the Covid-19 pandemic in Pekanbaru City - Fahmi Iqbal Firmananda; Zulfan Ependi; Dhya Nadia Laowe; Bustami Bustami (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2023)
Covid entered Indonesia for the first time in March 2020 Covid-19 entered Indonesia for the first time in March 2020, in Indonesia almost every sector has experienced an impact, one of which is the community's economic sector. The economic downturn in Indonesia resulted in a decline. One of the people's economies, namely Micro, Small and Medium Enterprises (MSMEs), is impacted by the Covid-19. In this study, the founder of the Al-Mahdi Pekanbaru outlet, namely Dinawati, was founded in 1998 in the city of Pekanbaru. This is the first kemojo cake business in Riau. The outlet produces and markets kemojo cake, a typical food from Riau Province. This business was initiated at the age of 24, after Covid-19 hit Indonesia, it had a negative impact, decreased turnover, termination of employment, increased raw materials, added to the enactment of social distancing and large-scale social restrictions (PSBB). The need to adapt to digital transformation using and utilizing social media in supporting business continuity. In Research Ni Made, et al 2021) This study aims to understand the importance of the right digital transformation model for every SME business, especially in taking advantage of the accelerated momentum due to the social restriction policy imposed during the COVID-19 pandemic, because choosing the right model is believed to provide probabilities which is better than a successful transformation. The results of this study are the success in implementing digital transformation by utilizing e-commerce, social media and online transportation such as go-jek with go-food features.